(y - 5)/3 = 1
y - 5 = 3 x 1 = 3
y = 3 + 5 = 8
6x + 29 = 5
6x = 5 - 29 = -24
x = -24/6 = -4
3/5*3/3=9/15
1/3*5/5=5/15
15 is a common denominator.
X/2+1/3=x/3+1/2
x/2=x/3+1/2-1/3
x/2 - x/3 = 3/6 - 2/6
x/2 - x/3 = 1/6
3x/6 - 2x/6 = 1/6
x/6 = 1/6
x = 1/6 * 6
x = 1
Answer:
Step-by-step explanation:
Let the numbers be
Such that:
Make z the subject
For their product to be maximum, we have:
Substitute in
Open bracket
Differentiate w.r.t x and y
Since the products are maximum, then
For
Factorize:
Split
Make y the subject
For
---------------------------------------------------
Substitute y = 0
Factorize
---------------------------------------------------
Substitute
Re-arrange
Factor x out
Divide through by x
Recall that:
Take LCM
Recall that:
Take LCM
Hence, the numbers are: